What Do We Want from Artists’ Houses? A Reflection - Christopher Reed (British Art Studies, 2018)
This article, based on a plenary lecture for the conference Alma-Tadema: Antiquity at Home and on Screen, explores the attractions of the artist’s house as a site of display in the late Victorian era, the early twentieth century, and today. Comparing the houses of Lawrence Alma-Tadema and Frederic Leighton with Charleston Farmhouse, home of the Bloomsbury artists Vanessa Bell and Duncan Grant, I invoke the comments of viewers from Walter Sickert to Patti Smith in order to examine the relationship between the look of surfaces and viewers’ perceptions of psychological depth.